Dental care of Anne d'Alègre (1565–1619, Laval, France). Between therapeutic reason and aesthetic evidence, the place of the social and the medical in the care in modern period. (April 2023) - Colleter, Rozenn; Galibourg, Antoine; Treguier, Jérôme; Guiavarc'h, Mikaël; Mare, Éric; Rigaud, Pierre-Jean; Destruhaut, Florent; Telmon, Norbert; Maret, Delphine
Highlights: 17th century prosthesis and ligature found on an identified archaeological body. Use of modern digital dentistry tools to resolve anthropological issues. Use of periodontal diagnosis classification stage/grade on anthropological material. Dental care in the provincial aristocracy of the French modern period: therapeutic, aesthetic and social motives. Abstract: Analysis of the oral cavity of human archaeological remains can provide essential information on the general health status of the person. The objectives of this paper are (i) to highlight an analysis of the oral state of the embalmed body of a 17th century female aristocrat with modern techniques of periodontal diagnosis and (ii) to provide a description of the therapeutic and aesthetic management intended to limit the functional and aesthetic consequences of the loss of teeth related to this periodontal disease. This paper provides the first demonstration of a link between a diagnosis and a therapy on an identified individual using new digital technologies used in modern dentistry. We propose that the objective of the treatment was triple: therapeutic, aesthetic and societal. Beyond the only therapeutic care and far from the only coquetry, this study shows also the importance of the appearance for aristocratic women submitted to strong social constraints (like stress or widowhood), the speech of the disfigured women being could be regarded as depraved.